2004
DOI: 10.1074/jbc.m311769200
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 Knockdown by Small Interfering RNA Suppresses Responses to the Chemokine Monocyte Chemoattractant Protein-1 by Human Astrocytes

Abstract: Astrocytes regulate the integrity of the blood-brain barrier and influence inflammatory processes in the central nervous system. The pro-inflammatory chemokine monocyte chemoattractant protein-1 (MCP-1), which is both released by and stimulates astrocytes, is thought to play a crucial role in both these activities. Because astrocytes have been shown to possess caveolae, vesicular structures that participate in intracellular transport and signal transduction events, we reasoned that expression of the major stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 63 publications
1
49
0
Order By: Relevance
“…Strong affinity interactions result in slow recycling or degradation, while low affinity interactions may result in rapid recycling [100][101][102]. Interestingly, studies on the chemotactic protease-activated receptor-2 (PAR-2) demonstrate that the receptor utilizes a β-arrestin-dependent mechanism to sequester activated ERK1/2 in the pseudopodia [47]. This raises the possibility that intracellular trafficking of chemokine receptors mediated by β-arrestin may have important implications for localization of signals.…”
Section: A Role For β-Arrestin In Chemokine Receptor Recyclingmentioning
confidence: 99%
See 2 more Smart Citations
“…Strong affinity interactions result in slow recycling or degradation, while low affinity interactions may result in rapid recycling [100][101][102]. Interestingly, studies on the chemotactic protease-activated receptor-2 (PAR-2) demonstrate that the receptor utilizes a β-arrestin-dependent mechanism to sequester activated ERK1/2 in the pseudopodia [47]. This raises the possibility that intracellular trafficking of chemokine receptors mediated by β-arrestin may have important implications for localization of signals.…”
Section: A Role For β-Arrestin In Chemokine Receptor Recyclingmentioning
confidence: 99%
“…However, non-specific effects of cholesterol depletion cannot be ruled out. In addition, studies conducted in astrocytes reveal that the inhibition of CCL2-triggered down-modulation and internalization of CCR2 by knocking down caveolin-1, a key component for caveolae, significantly inhibits chemotaxis and calcium mobilization [47].…”
Section: Role Of Lipid Rafts/caveloae In Chemokine Receptors Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that CCR5 internalisation can be inhibited by treatment with sucrose, nystatin and filipin, which inhibit clathrin-coated pit internalisation and affect caveolae in the cell membrane, respectively [2]. There have been reports about a number of receptors, like CCR4 [3] or CCR2 [4] where caveolae are important for receptor internalisation. Furthermore it has been reported that chemokines bind preferentially to receptors which are associated with cholesterol and sphingolipid-rich 3 lipid raft microdomains in the plasma membrane [5].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, in order to evaluate the effect of Caveolin-1 downregulation on the oncogenic transformation of normal HDFs, TIG3/TSR and BJ/TSR cells were transduced with a retroviral vector expressing a short interfering dsRNA for caveolin-1 (shCav422) (Ge and Pachter, 2004). These transduced cells were then selected with zeocine, resulting in a bulk population of (Figure 3a).…”
mentioning
confidence: 99%